Implikasi Risiko Politik Dan Ekonomi Terhadap Penganggaran Modal Perusahaan Multinasional di Indonesia - Siti Lailatur Rohmah; Anggita Della Lestari; Dhika Nurrohman; Muhammad Aswad (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This study examines how political and economic risks impact the capital budgeting processes of multinational corporations (MNCs) operating in Indonesia. Using a descriptive-analytical qualitative method, the research examines secondary data from academic journals, company financial reports, policy documents, and case studies on Mitsubishi, Daihatsu, PT Kalbe Farma, and PT Unilever Indonesia. The findings indicate that political instability—characterized by policy changes and bureaucratic complexity—and economic risks, such as fluctuations in exchange rates and inflation, significantly affect investment certainty, cash flow estimation, and capital costs. MNCs respond by adjusting investment strategies, forming local partnerships, and applying adaptive risk mitigation, with larger firms using more complex risk-based evaluation. The study enriches literature by integrating political and economic risk analysis into capital budgeting in developing countries. Limitations include reliance on secondary data and limited case studies, so results should be generalized cautiously. Practical implications highlight the importance of risk integration in investment decisions and government support for a stable investment climate.